Influence of interim cements on the optical properties of interim restorations - Correia, Ayla Macyelle de Oliveira [UNESP]; Borges, Alessanda Buhler [UNESP]; Caneppele, Taciana Marco Ferraz [UNESP]; Torres, Carlos Rocha Gomes [UNESP] (Elsevier, 2019)
Statement of problem: Even if the appropriate resin shade is selected for an interim restoration, how the optical characteristics of the interim cement affect the esthetics of the interim restoration is unclear. Purpose: The purpose of this in vitro study was to evaluate the effects of interim cements on the optical properties of interim restorations. Material and methods: Twenty dentin disks (6×1 mm) were obtained from the labial surface of bovine incisors. Disks of acrylic and bis-acrylic resins (n=20) with the same dimensions were prepared and cemented over the dentin using the following cements: Bifix Temp (resin-based; VOCO), ClearTemp LC (resin-based; Ultradent Products, Inc), Provicol (VOCO), TempCem NE (Coltène). The same dentin and resin disks were used for all cements. After cementation, the color difference (ΔE 00 ), translucency parameter (TP), and fluorescence of the dentin/cement/resin combinations were compared with each other and with a control group (C), in which a transparent liquid (polyethylene glycol 400; LabSynth) was applied. Color and translucency were evaluated with a spectrophotometer (CM-2600; Konica Minolta) and fluorescence with a spectrofluorophotometer (RF-5301PC; Shimadzu). ΔE 00 and TP data were analyzed using 2-way ANOVA. For fluorescence, 1-way ANOVA was used. The Tukey test was used for multiple comparisons (α=.05). Results: ΔE 00 values were significantly influenced by the interim material (P<.001) and the interim cement (P<.001). Bifix Temp showed the lowest significant ΔE 00 values (P<.001). The highest ΔE 00 values were observed for TempCem NE. No differences were observed between the interim resins with respect to TP (P=.318). The lowest translucency values were measured for TempCem NE, followed by Provicol, ClearTemp LC, Bifix Temp, and the control group (P<.001), with no significant differences among the interim resin-based cements. Among the cements, Bifix Temp and TempCem NE yielded fluorescence similar to that of the natural tooth for both interim resins. A similar result was found for bis-acrylic resin combined with Provicol. Conclusions: Cementation with interim resin-based cements resulted in better esthetics. However, the high fluorescence of the ClearTemp LC may reduce the esthetics of interim restorations in environments with predominantly UV light.